Long‐term continuity of steppe grasslands in eastern Central Europe: Evidence from species distribution patterns and chloroplast haplotypes. (4th October 2021) - Willner, Wolfgang; Moser, Dietmar; Plenk, Kristina; Aćić, Svetlana; Demina, Olga N.; Höhn, Maria; Kuzemko, Anna; Roleček, Jan; Vassilev, Kiril; Vynokurov, Denys; Kropf, Matthias
Abstract: Aim: The steppe grasslands of eastern Central Europe are exceptionally species rich and valuable from a nature conservation point of view. However, their historical biogeography is still poorly understood. Here we use the regional diversity of habitat specialists and chloroplast DNA data to investigate potential long‐term refugia of steppe species in this region. Location: Pannonian Basin and adjacent regions; SW Russia. Taxon: Vascular plants. Methods: After identifying habitat specialists of the three main steppe types (meadow steppes, grass steppes and rocky steppes), we compiled their regional presence–absence in grid cells of 75 km × 75 km. We analysed the dependency of habitat specialist diversity to climate, topographic heterogeneity and geographical distance to potential refugia. For genetic analysis, we sampled three or four habitat specialists of each steppe type and used cpDNA markers to investigate intraspecific diversity and geographical distribution of haplotypes. We also tested for correspondence between the number of habitat specialists and haplotype diversity. Results: Climate and topography explained between 40% and 63% of the variance in habitat specialist diversity. Adding geographical distance to potential refugia increased the explained variance in the models for all steppe types. Chloroplast haplotypes featured a complex pattern across the study area. Several species showed a strong geographical differentiation, suggesting migration waves from multiple refugia with only limited subsequent genetic intermixture. Maximum haplotype diversity in a region showed a better correlation with the number of habitat specialists per steppe type than mean haplotype diversity. Main conclusions: We can clearly reject the scenario of a late‐Holocene immigration of steppe species from areas outside the Pannonian Basin. Most species must have been present in the region since at least the early Holocene, highlighting the importance of the lower mountain ranges surrounding the Pannonian Basin as long‐term refugia for European steppe species. Dispersal limitation and resulting migration lags seem to have a strong influence on the distribution of steppe species in Central Europe.